Experimental studies of long-term fatigue of steel sewer structures - Maksimov, Serhii; Makarenko, Valerii; Vynnykov, Yuriy; Makarenko, Yulia (Academic journal Industrial Machine Building Civil Engineering, 2020)
The results show that the experimental studies of long-term fatigue (strength) of steel structures of underground sewage structures in a chemically aggressive environment, simultaneously containing chemical ingredients and biologically aggressive bacteria. It is established that long-term fatigue (strength) of steel structures of underground sewage structures is significantly reduced during long-term operation, and especially when exceeding 20 years or more, in chemically aggressive environments of domestic sewage, which often leads to corrosion and mechanical damage. It is shown that in the course of long service life the indicators of long-term fatigue of reinforcing steel rods of reinforced concrete structures are significantly reduced, which causes the formation of cracks in the connection "reinforcement - concrete", which usually leads to the destruction of reinforced concrete pipes and structures as a whole.